2015
DOI: 10.3201/eid2103.141313
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin Prophylaxis against MDR TB, New York, New York, USA

Abstract: Contacts of persons infected with multidrug-resistant tuberculosis (MDR TB) have few prophylaxis options. Of 50 contacts of HIV- and MDR TB–positive persons who were treated with moxifloxacin, 30 completed treatment and 3 discontinued treatment because of gastrointestinal symptoms. Moxifloxacin was generally well-tolerated; further research of its efficacy against MDR TB is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A registry match study [39] reporting results of MOX or PZA/MOX MDR-LTBI treatment regimens used in 2 outbreaks, mostly among persons with HIV, in New York City was published 3 months after completion of our systematic review, but would have been excluded from our meta-analysis because it was a registry match. Of those started on MDR-LTBI treatment, 60% (30/50) completed treatment and 6% (3/50) stopped due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A registry match study [39] reporting results of MOX or PZA/MOX MDR-LTBI treatment regimens used in 2 outbreaks, mostly among persons with HIV, in New York City was published 3 months after completion of our systematic review, but would have been excluded from our meta-analysis because it was a registry match. Of those started on MDR-LTBI treatment, 60% (30/50) completed treatment and 6% (3/50) stopped due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, it would take 2–5.5 years to detect 1 incident MDR-TB case (Supplementary Appendix). Attamna et al [7], Feja et al [8], and Trieu et al [39] used registry matches and found no related incident MDR-TB cases. Because MDR-TB is so rare in low-incidence settings and occurs largely in foreign-born persons, it is possible that moves/relocations resulted in no matches.…”
Section: Discussionmentioning
confidence: 99%
“…In this study [16] of the 50 contacts, initiating moxifloxacinbased prophylaxis in the 2 outbreaks, 30 (60%) completed treatment. Therapy was generally well-tolerated.…”
Section: Importance Of the Studymentioning
confidence: 70%
“…• The likelihood that the contact is newly infected with prophylaxis for the HIV patients with contact history of MDR-TB or suspected MDR-TB patient. The basis of this trial is based on recent study of contacts treated with moxifloxacin-or levofloxacin-based prophylaxis given to the MDR-TB contacts in 2 MDR-TB out breaks [16]. The study found no serious adverse events and fewer cases of disease among those treated than those untreated.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…For household contacts of patients with MDR-TB or XDR-TB (MDR-TB with added resistance to fluoroquinolones and second-line injectable agents) there are only observational studies to guide recommendations [44][45][46][47]. The drugs used for MDR-TB contacts have been mainly fluoroquinolones with or without other drugs such as ethambutol or ethionamide.…”
Section: Tb Preventive Therapy Regimensmentioning
confidence: 99%